2020
DOI: 10.1097/eja.0000000000001245
|View full text |Cite
|
Sign up to set email alerts
|

A nebulised antitumour necrosis factor receptor-1 domain antibody in patients at risk of postoperative lung injury: A randomised, placebo-controlled pilot study

Abstract: BACKGROUND Tumour necrosis factor receptor 1 (TNFR1) signalling mediates the cell death and inflammatory effects of TNF-α. OBJECTIVE The current clinical trial investigated the effects of a nebulised TNFR1 antagonist (GSK2862277) on signs of lung injury in patients undergoing oesophagectomy. DESIGN Randomised double-blind (sponsor unblind), placebo-controlled, parallel group study. SETTING Eight secondary care cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Significant reductions in the concentrations of inflammatory cytokines were also observed in bronchoalveolar lavage and serum [38]. In contrast, prophylactic treatment of a single dose of GSK2862277, a modified version of GSK1995057, did not reduce the postoperative alveolar capillary leak in patients following oesophagectomy [93]. The therapeutic potential of anti-TNFR1 dAb in ALI requires further investigation.…”
Section: Inhaled Mabs and Antibody Fragmentsmentioning
confidence: 95%
See 2 more Smart Citations
“…Significant reductions in the concentrations of inflammatory cytokines were also observed in bronchoalveolar lavage and serum [38]. In contrast, prophylactic treatment of a single dose of GSK2862277, a modified version of GSK1995057, did not reduce the postoperative alveolar capillary leak in patients following oesophagectomy [93]. The therapeutic potential of anti-TNFR1 dAb in ALI requires further investigation.…”
Section: Inhaled Mabs and Antibody Fragmentsmentioning
confidence: 95%
“…Therefore, an antibody derivative (GSK2862277) with reduced binding frequency to HAVH autoantibodies was produced and investigated in clinical trials. A single dose of inhaled GSK2862277 was well tolerated in patients with risk of ALI [93].…”
Section: Pegylationmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, TNFa is implicated in VALI with evidence that the blockade of TNFa is protective ( Proudfoot et al, 2018 ; Bertok et al, 2012 ). A phase II human trial of anti-TNFa was stopped due to being underpowered ( Ryan et al, 2020 ); however, this was recent, and so far no further human trials have been published. TNFa mediates its actions mainly through the NFkB pathway ( Liu et al, 2000 ; Zhang et al, 2017 ), and REVERB agonists have been shown to target this intracellular cascade, for example by binding to p65 at its promoter in macrophages ( Wang et al, 2018 ).…”
Section: Clock Genes As Targets For Lung Injurymentioning
confidence: 99%
“…With modern surgical and anesthesia care including minimally-invasive approaches, protective mechanical ventilation and avoidance of excessive hydration, the risk to damage the capillary-alveolar barrier is attenuated as shown by limited shedding of the EGL, small increase in extravascular lung water and in permeability vascular index after thoracic procedures. [ 45 46 ]…”
Section: Perioperative Fluid Optimizationmentioning
confidence: 99%